Achieving Optimal Therapeutic Hypothermia on Transport. (October 2016) - Schump, Elizabeth; Lancaster, Thomas; Sparks, Diane; Weatherstone, Kathleen; Holcomb, Robert
Abstract : Background: Early initiation of therapeutic hypothermia (TH) for the treatment of hypoxic ischemic encephalopathy (HIE) has been shown to improve outcomes. Many of these patients require transport to treatment facilities. At the time of the study, there were no servo-controlled devices approved for flight that allowed for active cooling of the neonate during air transport. Purpose: To introduce a clinical bundle for safe, active, or passive cooling and to achieve targeted, accurate temperature control with application for air or ground transport. Methods: After meeting criteria, a facsimile is sent to the referring center with instructions for passive cooling. Strict protocols are initiated, guiding the transport team in reaching and maintaining target temperature range of 33°C to 35°C. Results: From June 2010 to January 2014, a total of 22 neonates who qualified for TH were transported using the care bundle. Eight were actively cooled, whereas 14 were passively cooled. Of note, 8 infants required warming for temperatures below the acceptable range. The average temperature before turning off the warmer at the referral center was 36.0°C (SD = 1.1). The average temperature upon arrival of the transport team was 34.9°C (SD = 1.4). The average temperature upon arrival to the receiving facility was 33.5°C (SD = 0.7). Implication for Practice: By utilizing a care bundle for the initiation of TH on transport, neonates can be safely delivered to a treatment center with an average temperature well within treatment range, all while avoiding extreme fluctuations. Implications for Research: The number of qualified participants limited the study. Future research should focus on the effectiveness of the bundle in larger treatment populations, with inclusion of additional transport teams.